The Effect Of Implementing The Reading Aloud Method To Improve Students' Reading Skill - Ramlah, Samsul; Bahtiar, Yuyun (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study is motivated by the importance of reading skills for elementary school students as a foundation for understanding various subject matter, especially skills in understanding the contents of reading. One way that can be done is to carry out reading activities with the reading-aloud method. Reading aloud is an activity of reading aloud carried out by parents or teachers to children. This study aims to determine students' skills in understanding the contents of reading and students' perceptions of the reading aloud method. The research approach used is a quantitative approach with a Pre-Experimental Design research type. The independent variable in this study is the reading aloud method while the dependent variable is students' reading skills. The population is 25 students from all grade II students. The research sample was selected using the simple saturated technique. Data collection techniques used in this study are observation, testing, and documentation. Data were collected from the provision of pretests, treatments, and posttests then analyzed using descriptive statistics and inferential statistics using the Paired Sample Test using the IBM SPSS Statistic Version 25 system. The results of this study indicate that (a) the reading-aloud method can be applied well by teachers and is carried out according to the stages that should be, (b) Reading skills before and after using the reading-aloud method have increased. The application of the reading-aloud method has a significant influence on the reading skills of class II students of SD IT Qurthuba.